1985
DOI: 10.1111/j.1468-0092.1985.tb00247.x
|View full text |Cite
|
Sign up to set email alerts
|

The Place of Chronological Studies in Archaeology a View From the Old World*

Abstract: This article deals with the univeral problem of chronological versus social change and discusses the methodological foundations and the scientific functions of chronological studies, exemplified by the Nordic Bronze Age, a classic example of the development of a chronological system. First the universal validity of the premises of typology and seriation are questioned. Secondly, there is a discussion of the chronological implications of the many possible relationships between the period of production, the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…This, however, was always a rhetorical analogy -a metaphor. I discussed this problematic with some Bronze Age examples many years ago and demonstrated that variations in typological change -innovation versus tradition -could always be linked to social and economic conditions (Kristiansen 1985).…”
Section: To Be Challenged or Not -That Is The Questionmentioning
confidence: 99%
“…This, however, was always a rhetorical analogy -a metaphor. I discussed this problematic with some Bronze Age examples many years ago and demonstrated that variations in typological change -innovation versus tradition -could always be linked to social and economic conditions (Kristiansen 1985).…”
Section: To Be Challenged or Not -That Is The Questionmentioning
confidence: 99%